Work Life Balance Dengan Kepuasan Kerja Pada Karyawan Penambang PT Bukit Asam - Aldy Rachmadi; Nuzsep Almigo (Universitas Darul Ulum, 2026)
Mining sector employees are vulnerable to work-life imbalance due to 24-hour shift systems and remote locations, which can reduce job satisfaction. This study aims to analyze the relationship between work-life balance and job satisfaction among mining employees at PT Bukit Asam Tbk in Tanjung Enim. A quantitative correlational approach was used with simple linear regression analysis. A total of 70 employees from three mining units were selected using purposive sampling, with self-report scales measuring dimensions of time balance, involvement balance, satisfaction balance, salary, working conditions, promotion, supervision, and coworker relations. Results revealed a positive and significant relationship between work-life balance and job satisfaction, with work-life balance contributing 85.8% to the variation in job satisfaction. These findings imply that organizational policies supporting work-life balance are essential strategies for improving employee well-being and productivity in the mining sector.